A template method for measuring the iron spectrum in cosmic rays with Cherenkov telescopes. (July 2015) - Fleischhack, Henrike
Abstract: Understanding the sources, acceleration mechanisms, and propagation of cosmic rays is an active area of research in astro-particle physics. Measuring the spectrum and elemental composition of cosmic rays on earth can help solve this question. IACTs, while mainly used for γ-ray astronomy and indirect searches for dark matter, can make an important contribution here. In particular, they are able to distinguish heavy nuclei in cosmic rays from protons and lighter nuclei by exploiting the direct Cherenkov light emitted by charged particles high in the atmosphere. In this paper, a method to reconstruct relevant properties of primary cosmic ray particles from the Cherenkov light emitted by the primary particles and the air showers induced by them will be presented.